Political Education for Muhammadiyah Youth Cadres in Batu City - Roziqin, Ali; Widodo, Eko Rizqi Purwo; Mas'udi, Syasya, Y.F; Camico, Danang B.; Khoirunnisa, Kamila (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2025)
Political awareness among youth is often low, which impacts their participation in the democratic process. Youth have great potential to contribute to political development, but a lack of knowledge and skills often hinders their participation. Taking the object of the Muhammadiyah generation represented by the Muhammadiyah Student Association in Batu City, this service aims to improve youth understanding of the political and democratic process which has an impact on active participation in “adiluhung politics”. Through this education there is a process of transfer of knowledge and active political participation, especially for groups of young voters in the 2024 elections and politics universally. We have done this service and received a positive impression from the participants. Participants discussed the dynamics of current national politics and the unrest of youth groups to participate in practical politics with just noble values. Keywords: Political Education, Political Participation, Local Elections, Muhammadiyah Youth